Staphylococcal skin infection isolates from dogs without recent antibiotic exposure are 100% susceptible to clindamycin - Brookshire, W. Cooper; Ballard, Larry D.; Langston, Vernon C.; Park, Joo Youn; Seo, Keun-Seok (Frontiers in Veterinary Science, 2025)
The objective of this study was to create an antibiogram representative of bacterial skin infections in canine patients that would typically be treated empirically, i.e., without risk factors for antibiotic resistance, such as a history of recent antibiotic use, antibiotic treatment failure, or recurrent infections. Traditional antibiograms are a form of passive surveillance and report antibiotic susceptibility of isolates from a specific laboratory, hospital, or region for a given period of time. However, traditional antibiograms are biased towards more resistance, because infections that have antibiotic susceptibility tests are more likely to be resistant, due to risk factors such as recent antibiotic treatment, hospitalization, or a history of previous antibiotic-resistant infections. Antibiotic susceptibility testing was performed on 67 pathogenic canine staphylococcal isolates (62 Staphylococcus pseudintermedius and 5 Staphylococcus schleiferi) from patients who met the study inclusion criteria, and 100% of isolates were susceptible to antibiotics commonly prescribed for canine staphylococcal skin infections, including clindamycin. Additionally, a subset of 49 isolates were also susceptible to chlorhexidine. The isolates were susceptible to a very low concentration of chlorhexidine, which supports its use as a preferred topical treatment. These data strongly indicate that dogs without a history of recent antibiotic use, treatment failure, or recurrent infections that present with bacterial skin infections are at low risk of antibiotic resistance. If systemic antibiotics are indicated in these patients with this clinical history and presentation, clindamycin should be considered as first-line therapy, owing to its 100% susceptibility in this antibiogram and less selection pressure for antibiotic resistant bacteria, compared to alternatives such as cephalosporins.